2014
DOI: 10.1371/journal.pone.0084587
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mass in Dialysis Patients, Determinants and Relation with Outcome. Results from the COnvective TRansport STudy (CONTRAST)

Abstract: Background and ObjectivesLeft ventricular mass (LVM) is known to be related to overall and cardiovascular mortality in end stage kidney disease (ESKD) patients. The aims of the present study are 1) to determine whether LVM is associated with mortality and various cardiovascular events and 2) to identify determinants of LVM including biomarkers of inflammation and fibrosis.Design, Setting, Participants, & MeasurementsAnalysis was performed with data of 327 ESKD patients, a subset from the CONvective TRAnsport S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
1
23
0
1
Order By: Relevance
“…Previously, we showed that patients with a high LVM are at increased risk for all-cause mortality, cardiovascular mortality and sudden death [15]. These findings were confirmed in the present investigation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previously, we showed that patients with a high LVM are at increased risk for all-cause mortality, cardiovascular mortality and sudden death [15]. These findings were confirmed in the present investigation.…”
Section: Discussionsupporting
confidence: 91%
“…Given this high occurrence rate, identification of risk factors for sudden death and, thus possibly, opportunities for preventive interventions seem highly required. As LVH is a well-established risk factor for all-cause and cardiovascular mortality and, particularly, for sudden cardiac death [15], the question arises whether clinical outcome is dissimilar for ESKD patients with different types of LVH, that is, eccentric or concentric LVH. To address this question, data from the CONvective TRAnsport STudy (CONTRAST) were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…general population, coronary artery disease and CHF are not the major risk factors in dialysis patients (16). In prevalent HD patients, LVH was associated with sudden death (17,18); in another study of PD patients, systolic dysfunction was the most significant predictor followed by a high systolic BP (24). These results might explain the association of low T3 syndrome with sudden death considering that low T3 was associated with left ventricular dysfunction and LVH in a previous study (7).…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, when taken as a single cause, sudden death accounts for onequarter of all dialysis patients' deaths (16). Left ventricular hypertrophy (LVH), left ventricular systolic dysfunction, and aortic stiffness are known to be risk factors for sudden death (16)(17)(18), and are also significantly associated with low T3 syndrome (7,9,10) in dialysis patients. Considerable evidence has raised the possibility that low T3 syndrome may be a predisposing factor for sudden death, but the relationship between the two has not yet been determined in PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…5,22 The close association between inflammation, hypoalbuminemia and OH was also confirmed by other studies, which found inflammation and hypoalbuminemia being the strongest determinants of OH. 23,24 On one hand, malnutrition and low albumin level contribute to systemic inflammation through tissue OH, while on the other hand, as a result of a kind of vicious circle, chronic inflammation leads to hypoalbuminemia, and ultimately to OH. 4,25 Furthermore, diabetes and diabetic nephropathy may be an additional risk factor for malnutrition in PD patients.…”
Section: Parametersmentioning
confidence: 99%